Utilizing Vulnerability and Risk Indexes for Cultural Heritage in Yogyakarta and Central Java - Hizbaron, Dyah Rahmawati; Lukafiardi, Radikal; Aprilianti, Christina; Jati, Raditya (Universitas Muhammadiyah Surakarta, 2020)
Indonesia is home to many cultural heritages which are exposed to natural disaster, its number has grown by 400% within the years of 1975-2010.Â In order to protect the cultural heritages, the national government released InaRisk â€“ a web based geospatial data to identify risk information. This application, however, not fully apprises its users of the potential loss that cultural heritage objects, especially temples, may sustain. For these reasons, the research set out to evaluate the potential loss of temples by making use of disaster vulnerability and risk approaches. Seven temples were exposed to earthquake and landslide hazards; hence, observed as the research object on a micro-scale. The research method combined tabular, spatial, and temporal data of several indicators, namely types of building materials, buildingâ€™s structural integrity after earthquakes and landslides, the number of salvageable objects, building age, significance, historical value, and the number of visitors. The results showed that Prambanan and Sewu Temples had the most substantial amounts of potential losses incurred from damages to at-risk elements, namely the numbers of visitors, employees, and supporting facilities and their distances to sources of hazards. Assessing the numerical values of losses requires further improvements in accuracy as it has not thoroughly factored in the significance of the temples, which is composed of historical value, building age, number of visitors, and other components. Valuation of this significance is still limited to currently available data, including the price of the constituent rocks, area and volume, and supporting facilities.